Detection and identification of Lactobacillus helveticus bacteriophages by PCR - Zago, Miriam (2008)
A PCR protocol for detection of Lactobacillus helveticus bacteriophages was optimized. PCR was designed taking into account the sequence of the lys gene of temperate bacteriophage W-0303 and optimized to obtain a fragment of 222 bp using different Lb. helveticus phages from our collection. PCR was applied to total phage DNA extracted from 53 natural whey starters used for the production of Grana cheese and all gave the expected fragment. The presence of actively growing phages in the cultures was verified by traditional tests. Several PCR products of the lys gene were sequenced and aligned. The resulting sequences showed variable heterogeneity between the phages.